UV-B RADIATION INDUCED ALTERATIONS IN PHOTOSYNTHETIC ELECTRON TRANSPORT ACTIVITIES OF THE THYLAKOID MEMBRANES OF BARLEY PRIMARY LEAVES - S. D. SUDHEER,; M. AYYA RAJU,; S. D. S. MURTHY, (The Bioscan, 2011)
Ultraviolet- B radiation induced changes in the photochemical activities of the thylakoid membranes isolated from barley primary leaves have been characterized by using polarographic studies through oxygen electrode. UV- B radiation (2 - 8 Wm-2) caused inhibition in whole chain electron transport as well as photosystem II catalyzed electron transport activities in an intensity dependent manner. Almost 50% inhibition was noticed in the above catalyzed electron transport activities after the exposure of 4 Wm-2 for 30 min. The reason for the loss PS II activity could be alteration at the level of water oxidation complex. Contrary to the above, PS I catalyzed electron transport less sensitive to UV-B radiation (2 - 8 Wm-2) and even at 8 Wm-2 only 20% loss was observed. But the measurement of intersystem electron transport mediated by DQH2 showed that intersystem electron transport carriers like plastoquinone is sensitive to UV–B radiation and 40% loss was observed at 8 Wm-2 of UV-B. Thus UV-B radiation exerts multiple effects on photosynthetic electron transport based on the intensity of exposure in barley leaves.